Evaluation and Design of Production Scheduling PT. Hume Sakti Indonesia - yogi, Angga wahyu prima; Widodo, Arifin Puji; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
AbstractPT. Hume Sakti Indonesia is one of the poles and power lines with a production system that is used is a pull system that only do production if there is an order from the customer. In such conditions when there is a production order is entered suddenly with a relatively short deadline often Production Division more production priority orders that have a time limit shorter than the first order entered by the deadline of length, and the material used for other orders, such as cement, sand, stone and aggregate, used to serve the order suddenly with a short deadline. This resulted in frequent delays due to the absence of production scheduling system used by the company.The design evaluations are made scheduling production at PT. Hume Sakti Indonesia which produce production scheduling based on calculations using the rules of priority are four methods that can help the Division of Production and Warehouse in getting the best scheduling for the production process.Based on the results of experiments performed together with PT. Hume Sakti Indonesia, these applications generate output results of the evaluation of the production scheduling of a calculated four methods of using the rules of priority (FCFS, SPT, EDD, and LPT), reports penjawalan, reports the buyer's order, the production schedule per the contract, the production schedule monthly, schedule of material per contract, schedule of monthly materials, production instructions.Keywords: Production Scheduling, Evaluation of Production Scheduling, Rule Priority, Production Schedule and Production Instructions.